Grain Boundary Precipitation Control of GCP Phase Using TCP or A2 Phase in Ni-Based Alloys - Shuntaro Ida; Ryosuke Yamagata; Hirotoyo Nakashima; Satoru Kobayashi; Masao Takeyama (Metals, 2022)
To cover the grain boundary (GB) of the Ni phase with precipitates, the GB precipitation behavior of both topologically close-packed (TCP) or A2 and geometrically close-packed (GCP) phases was investigated in two Ni–Nb–(Co, Cr) ternary systems. The Ni/TCP or A2/GCP three-phase region existed in both systems. In the Ni-Nb-Co ternary system, Nb was approximately equally partitioned into both Co7Nb2 (mC18 structure, TCP) and (Ni, Co)3Nb (D019 structure, GCP) phases. In the Ni–Nb-Cr ternary system, Nb and Cr were mainly partitioned into the Ni3Nb (D0a structure, GCP) and Cr (A2 structure) phases, respectively. In the Ni–Nb–Co ternary system, the Co7Nb2 phase grew along the GB, whereas the (Ni, Co)3Nb phase grew toward the grain interior (GI). However, the growth of the Ni3Nb phase toward the GI was suppressed in the Ni–Nb–Cr ternary system. The suppression of growth of the GCP phase and covering the GB using both the TCP or A2 and GCP phases might be possible in a system where the precipitation of the GCP phase nucleating on the GB prior to the TCP or A2 phase increases supersaturation for precipitation of the TCP or A2 phase.